Decreased Peripheral BDNF Levels and Cognitive Impairment in Late-Life Schizophrenia - Huo, Lijuan; Zheng, Zhiwei; Lu, Xiaobing; Wu, Fengchun; Ning, Yuping; Zhang, Xiang Yang (Frontiers in Psychiatry, 2021)
Objectives: Although there is a large body of literature on mechanisms of cognitive deficits in adult schizophrenia, there are relatively few studies on late-life schizophrenia (LLS). Brain-derived neurotrophic factor (BDNF), as an important neuroplastic molecule, has been reported to be involved in neurocognitive impairment in schizophrenia. This study aimed to examine whether peripheral BDNF levels were associated with cognitive deficits in LLS, which has not been explored yet. Methods: Forty-eight LLS patients and 45 age-matched elderly controls were recruited. We measured all participants on the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) for cognition and serum BDNF levels. Psychological symptoms in all patients were assessed by the Positive and Negative Syndrome Scale (PANSS). Results: The levels of BDNF in LLS patients were significantly lower than those in normal controls (8.80 ± 2.30 vs. 12.63 ± 5.08 ng/ml, p < .001). Cognitive performance of LLS patients was worse than that of the controls on RBANS total score and scores of immediate memory, attention, language, and delayed memory (all p ≤ .005). BDNF was positively associated with attention in LLS patients (r = .338, p = .019). Conclusion: Our findings suggest that older patients with schizophrenia exhibit lower BDNF levels and more cognitive deficits than older controls, supporting the accelerated aging hypothesis of schizophrenia. Moreover, decreased BDNF is related to attention deficit, indicating that BDNF might be a candidate biomarker of cognitive impairments in LLS patients.